SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LOKASI PEMBANGUNAN HOTEL DENGAN METODE MULTI-ATTRIBUTIVE BORDER APPROXIMATION AREA COMPARISON - Muhammad Yunus; Elsida Aritonang; Victor Maruli Pakpahan; Jubelando O Tambunan; Doris Yolanda Saragih (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
This research aims to develop a Decision Support System (DSS) for determining the location of hotel development on Samosir Island. This DSS is constructed using the Multi-Attributive Border Approximation Area Comparison (MABAC) method. The criteria used in this study include Distance (C1), Natural Beauty (C2), Cleanliness (C3), Transportation (C4), and Atmosphere (C5). The choice of MABAC as the method is made because it provides flexibility for decision-makers to specify preferences and consider variations in criteria. The ranking results from MABAC indicate the top three locations, namely LH04, LH03, and LH01. By implementing the DSS using the MABAC method, this system is expected to make a significant contribution to optimizing the selection of hotel development locations in Samosir. The findings of this research illustrate that the use of the DSS with the MABAC method can be relied upon as a guide in addressing the impact of sustainable hotel growth in crucial tourist destinations such as Samosir.